2007
DOI: 10.1029/2007gl030836
|View full text |Cite
|
Sign up to set email alerts
|

Creep on the Rodgers Creek fault, northern San Francisco Bay area from a 10 year PS‐InSAR dataset

Abstract: Deformation in the northern San Francisco Bay area is dominated by a series of sub‐parallel strike‐slip faults. Existing GPS observations provide some constraint on the slip rates of these faults, however these have only limited resolution for resolving shallow fault behavior, such as brittle creep. We use a 30 image Permanent Scatterer InSAR (PS‐InSAR) dataset spanning the time interval 1992–2001 to dramatically increase the density of surface deformation observations. We find a discontinuity in observed surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 19 publications
7
66
2
Order By: Relevance
“…Finally, advanced InSAR processing such as PSInSAR has rendered an improved accuracy in mapping and characterisation of various natural hazards (e.g. Colesanti et al 2003, Hilley et al 2004, Lanari et al 2004, Farina et al 2006, Funning et al 2007, Bell et al 2008, Novali et al 2008, Puglisi et al 2008, Bianchi, 2009). …”
Section: Hazards Applications Of Insar Deformation Mapsmentioning
confidence: 98%
“…Finally, advanced InSAR processing such as PSInSAR has rendered an improved accuracy in mapping and characterisation of various natural hazards (e.g. Colesanti et al 2003, Hilley et al 2004, Lanari et al 2004, Farina et al 2006, Funning et al 2007, Bell et al 2008, Novali et al 2008, Puglisi et al 2008, Bianchi, 2009). …”
Section: Hazards Applications Of Insar Deformation Mapsmentioning
confidence: 98%
“…In addition, recent satellite-based permanent scatterer interferometric synthetic aperture radar (PS-InSAR) studies (Funning et al, 2007) suggest that to the northwest and southeast of the Santa Rosa pull-apart basin, the Rodgers Creek fault zone is undergoing as much as 7.5 ± 2.6 mm/yr of shallow creep above a depth of 6 km.…”
Section: Rodgers Creek Fault Zone Slip Ratesmentioning
confidence: 98%
“…The West Napa fault previously experienced an M 5 strike-slip event in 2000 but otherwise exhibited no previous definitive evidence of historic earthquake rupture (Rodgers et al, 2008;Wesling and Hanson, 2008). Evans et al (2012) found slip rates of ∼9:5 mm=yr along the West Napa fault, with most slip rate models for the Bay area placing higher slip rates and greater earthquake potential on the Rodger's Creek and Green Valley faults, respectively (e.g., Savage et al, 1999;d'Alessio et al, 2005;Funning et al, 2007).…”
Section: Introductionmentioning
confidence: 99%